DERIVATIONAL AFFIXES FORMING NOUN IN FIREFLY LANE NOVEL BY KRISTIN HANNAH - Ardiningsih, Ni Luh Putu; Sulatra, I Komang; Maharani, Putu Devi (Institut Hindu Dharma Negeri Denpasar, 2021)
This study aims to find out the types of derivational affixes forming noun and the functions of derivational affixes forming noun in the novel entitled Firefly Lane written by Kristin Hannah.Â The methods used in this study are quantitative and qualitative methods. This study used observation method in collecting the data from all chapters in the novel Firefly Lane.Finally, this writing concludes that there were two functions of derivational affixes such are: class changing affixes and class maintaining affixes and each function has two types which are: prefixes and suffixes. The result of the study found there are 3 prefixes forming noun such are: re-, pre-,andÂ pro-, and from suffixes there were found 22 suffixes forming noun, they are: -er, -hood, -ism, -ist, -ity, -ship, -ness, -th, -ize, -less, -ous, -y, -ful, -ive, -ing, -ance, -ence, -ant, -ion, -ment, - or, and â€“ure.